(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The growing adoption of electric bikes has transformed personal transportation, therefore, the study examines the quality of electric bikes and its impact on customer satisfaction and loyalty. The study collects 400 samples; primary data are collected from electric bike users using questionnaire. The demographic analysis reveals that electric bike usage is more prevalent among middle-aged, educated, and economically active customers. Factor analysis identified performance quality, durability, comfort, safety, economic efficiency, and after-sales support as key determinants of customer satisfaction. Regression results confirmed that these quality dimensions have a significant positive impact on satisfaction. The Friedman test stressed battery reliability, operating cost, and riding comfort as major drivers of customer loyalty. The study also reveals dangerous problems such as limited battery backup, long charging time, and inadequate charging infrastructure. Findings provide implications for manufacturers, service providers, and policymakers to enhance electric bike quality, strengthen customer loyalty, and promote sustainable mobility.